Heavy Metal Contamination in the Environment: Health Impacts and Potential Remediation Approaches - Singh V.; Kumar A.; Mishra V.; Rai S.N. (My University, 2025)
This reference book explores the multifaceted problem of heavy metal contamination in the environment. Through its in-depth analysis, the book provides a thorough overview of the sources and pathways of heavy metals, their persistence in ecosystems, and the resulting health impacts on individuals and ecosystems. The chapters explore the diverse sources of contamination, including industrial activities, mining, agriculture, and urbanization, while examining the types of heavy metals found in the environment and their toxicological properties. The book further reviews the profound health effects associated with heavy metal exposure, such as neurological disorders, developmental abnormalities, carcinogenicity, and organ damage. Furthermore, the book provides insights into risk assessment methodologies, regulatory frameworks, and guidelines aimed at controlling and minimizing heavy metal exposure. It highlights the challenges and gaps in current regulations, identifies potential areas for improvement, and presents analytical techniques for heavy metal analysis and removal. This book is an important source for researchers and professionals working in the fields of environmental science, toxicology, and public health. © 2025 selection and editorial matter Veer Singh, Ashish Kumar, Vishal Mishra and Sachchida Nand Rai; individual chapters, the contributors.